2020
DOI: 10.1097/corr.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

What Proportion of Patients Undergoing Bernese Periacetabular Osteotomy Experience Nonunion, and What Factors are Associated with Nonunion?

Abstract: Background The Bernese periacetabular osteotomy (PAO) is one of the most-used surgical techniques to treat symptomatic acetabular dysplasia. Although good functional and radiographic short-term and long-term outcomes have been reported, several complications after PAO have been described. One complication that may compromise clinical results is nonunion of an osteotomy. However, the exact prevalence and risk factors associated with nonunion are poorly elucidated. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Importantly however, there was no difference in patient-reported outcomes of pain or health-related quality of life. A previous large cohort study of patients undergoing PAO surgery for DDH, where no additional augmentation to improve bony healing was used, reported that only 45% (96 of 215) of the patients had complete healing of all osteotomy sites at the 6-month visit and 92% (225 of 245) demonstrated complete healing at 1 year [ 12 ]. While our findings suggest that the addition of a Peptide Enhanced Bone Graft might enhance bony healing, these need to be confirmed in a prospective RCT, and over longer follow-up times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly however, there was no difference in patient-reported outcomes of pain or health-related quality of life. A previous large cohort study of patients undergoing PAO surgery for DDH, where no additional augmentation to improve bony healing was used, reported that only 45% (96 of 215) of the patients had complete healing of all osteotomy sites at the 6-month visit and 92% (225 of 245) demonstrated complete healing at 1 year [ 12 ]. While our findings suggest that the addition of a Peptide Enhanced Bone Graft might enhance bony healing, these need to be confirmed in a prospective RCT, and over longer follow-up times.…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with PAO have been shown to adversely affect long-term pain and activity [ 5 ]. The most common major surgical complication following PAO is non-union [ 5 ], with over half of patients demonstrating incomplete healing of osteotomy sites at six-months post-operatively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fractures of the inferior pubic ramus (Figure 3) were indicated by the radiolucency or discontinuity at the ischial/inferior pubic ramus or at the ischiopubic junction (IPJ). 16,21 Union of the osteotomies was confirmed on AP radiological view of the pelvis on 12-month follow-up after surgery. Osseous union was confirmed if there was no visible radiolucent line and an uninterrupted trabecular pattern.…”
Section: Methodsmentioning
confidence: 86%
“…Fractures of the inferior pubic ramus (Figure 3) were indicated by the radiolucency or discontinuity at the ischial/inferior pubic ramus or at the ischiopubic junction (IPJ). 16,21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation